A contactless characterization of CNT/Epoxy nanocomposites behavior under acid exposure. (1st February 2023) - Tamayo-Vegas, S.; Lafdi, K.; Elsdon, M.
Abstract: The use of polymer nanocomposites is ubiquitous in every industry. The high corrosion resistance and chemical durability of CNT/Epoxy nanocomposites make them suitable for chemical plants, oil industries, and hydrogen storage. However, unexpected failures have been reported for chemicals that unavoidably penetrate, provoking deterioration and degradation of the composite constituents. Conventional methods are impractical for evaluating structural health conditions because they often require disassembly of the structure and complex post-processing analysis. Contactless material characterization methods, on the other hand, are rather promising tools. Nevertheless, the influence of nanofillers and acid attack diffusion on wireless signals has yet to be explored. In this study, the effects of acid attack periods (i.e. one, week, two weeks, and month) on the scattering parameters of microstrip antennas were investigated using a vector network analys. Additionally, an idealised multi-scale modelling approach was developed to study the influence of electrical conductivity and porosity volume changes on return loss (S11). The data showed that the diffusion of ions altered the specimen properties as time progressed. The increment in the electrical conductivity and porosity volume is reflected especially during the month-long period. Finally, in this study, it was found that wireless methods can be implemented to characterise materials which are beneficial for real-time in-situ structural health monitoring.